2010
DOI: 10.1111/j.1745-4549.2010.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Encapsulating Materials on Water Sorption Isotherms of Vacuum-Dried Persimmon Pulp Powder

Abstract: Water sorption isotherms for vacuum‐dried persimmon pulp (PP) powder were determined in the temperature range of 20–50C, and the effects of maltodextrin (MD) or gum arabic (GA) addition on the water sorption behavior of the dried powders were analyzed. Several models were evaluated to fit the experimental data and the Guggenheim‐Anderson‐de Boer model was selected as the most adequate to describe the observed behavior. Addition of encapsulants affected the isotherms: at the same water activity, PP powder with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Pedro et al (2010), observaram valores de atividade de água em torno de 0,206 em seus estudos com pós de polpa de maracujá adicionados de 55% de maltodextrina, obtidos por liofilização; este valor está muito próximo dos encontrados neste estudo. De acordo com Benedetti et al (2011), a adição de maltodextrina evitou a pegajosidade e aglomeração do pó de caqui durante o processamento e o armazenamento. As médias seguidas da mesma letra nas linhas não diferem estatisticamente pelo teste de Tukey, a nível de 5% de probabilidade.…”
Section: Resultsunclassified
“…Pedro et al (2010), observaram valores de atividade de água em torno de 0,206 em seus estudos com pós de polpa de maracujá adicionados de 55% de maltodextrina, obtidos por liofilização; este valor está muito próximo dos encontrados neste estudo. De acordo com Benedetti et al (2011), a adição de maltodextrina evitou a pegajosidade e aglomeração do pó de caqui durante o processamento e o armazenamento. As médias seguidas da mesma letra nas linhas não diferem estatisticamente pelo teste de Tukey, a nível de 5% de probabilidade.…”
Section: Resultsunclassified
“…The “cempedak” puree was spread out in a stainless‐steel tray at 1.5°C m thickness. The “cempedak” puree placed in a vacuum‐dryer (VD 23, Binder, Germany) at 70°C for 24 hr, at 1 bar pressure (Benedetti et al., 2010). After that, the obtained dried flakes were ground into powder using a mill grinder (MF10, IKA, Germany), with smallest grinder sieve of 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh fruits have a short shelf life. There are many methods for extending shelf life, such as drying and making fruit juice (Benedetti et al, 2011). Ergun and Ergun (2010) reported that the use of a honey dip solution prolonged the storage life of fresh persimmon based on the delay of off-aroma development.…”
Section: Introductionmentioning
confidence: 99%